Meraih Eco Design melalui Renovasi Rumah Tinggal - Hendrassukma, Dila (Humaniora, 2011)
The needs of up enhancing space qualities at home are often the reason to re-design a house. Nonetheless, the life needs that always changing make it hard to know how to create a house that can deliver spaces for the unknown future activities. These days, where resources are less than before, having a house alternation can also make the house more sustain and more energy efficient. Research is conducted to find way to realizing the idea of making a house greener through renovation. The methods used is by collecting and analyzing articles and books of eco design. The result is options of different approach to renovate a house by applying eco design strategies to achieve a sustainable and an energy efficient living space to be lived in today and in the future. Transform a regular house to become an eco house does not always make the renovation to be more complex, by understanding basic principals of eco design and get help from the professional an eco house can be achieved as a contribution to reduce causes of global warming.